Self-reported periodontal disease, dental loss and COVID-19 in older adults - Yamile Baganet Cobas; Alain Manuel Chaple-Gil; Yilian Caballero-Guerra; Dayana Chávez-Valdez (Revista Cubana de Medicina Militar)
Introduction: Upon completion of this research, there was no evidence of studies addressing self-reported periodontal disease in Cuba, nor any antecedent of research relating it to COVID-19 in adults over 60. Objective: To determine the relationship between self-reported periodontal disease, dental loss, and COVID-19 activity. Methods: A descriptive cross-sectional investigation was carried out. The sample included 238 individuals aged over 60 who were infected with COVID-19, and survived. They gave their consent. The study was performed for over 1 year in Playa municipality of Havana, Cuba. Variables such as gender, age, COVID-19 evolutionary severity, comorbidities, and self-reported periodontal disease were used. A validated 4-question survey was applied to identify the periodontal disease and all data were processed in a database. Some variables were dichotomized to perform the odds ratio and Pearson's Chi-squared test, and determine the relationship between possible risk factors and the evolutionary severity of COVID-19. Results: As a result, the odds ratio values and confidence intervals for periodontal disease and advanced periodontal disease were 1.598 (0.261; 9.78) and 1.814 (0.296; 11.105) respectively, and the p-values were 0.609 and 0.514 respectively. Conclusion: A relationship between periodontal disease and the evolutionary severity of COVID-19 cannot be established. However, a relationship was observed targeting dental loss and respiratory diseases as determinant risk factors in the severity of COVID-19.